Image acquisition system for boiler header inspection robot - How D.N.T.; Sahari K.S.M.; Anuar A.; Baharuddin M.Z.; Ghani M.F.A.; Aziz M.A. (Springer Verlag, 2023)
This paper aims to present development of an image acquisition in the task of power plant boiler header inspection. Among the content of this paper includes hardware selection and software selection and integration of both systems to form a complete image acquisition system. The real challenge behind the project is the miniature scale of the robot that will be used to carry the image acquisition system into the boiler header, since a boiler header entrance is normally only about 80 mm in diameter. Hardware system needs to be small enough to fit into the boiler header entrance. This paper also discusses the results from testing in Stesen Janakuasa Sultan Ismail, Paka as a verification of the workability of the designed system. © 2014 Springer Science+Business Media Singapore.